2017
DOI: 10.1155/2017/9082164
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Metal-Containing Diamond-Like Carbon Films by Magnetron Sputtering and Plasma Source Ion Implantation and Their Properties

Abstract: Metal-containing diamond-like carbon (Me-DLC) films were prepared by a combination of plasma source ion implantation (PSII) and reactive magnetron sputtering. Two metals were used that differ in their tendency to form carbide and possess a different sputter yield, that is, Cu with a relatively high sputter yield and Ti with a comparatively low one. The DLC film preparation was based on the hydrocarbon gas ethylene (C 2 H 4 ). The preparation technique is described and the parameters influencing the metal conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…A granular surface is again observed and the width of these features is slightly larger (40 nm ± 14 nm) compared to the corresponding a-C thin film (17.5 nm ± 5 nm). Several studies have reported that metal doping generally results in a change in grain size [21,49,50], as well as film density [51], where the latter depends on how the incorporated metal diffuses.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…A granular surface is again observed and the width of these features is slightly larger (40 nm ± 14 nm) compared to the corresponding a-C thin film (17.5 nm ± 5 nm). Several studies have reported that metal doping generally results in a change in grain size [21,49,50], as well as film density [51], where the latter depends on how the incorporated metal diffuses.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…It is known that depositing DLC films directly onto steel surfaces provides a poor-quality film because of high residual stress at their interfaces [2,4]. Therefore, an interlayer/multilayer deposition has been proposed to obtain high-quality DLC film [5,6]. Here, the Ti film is one of the most effective interlayers with good capability and suitability for DLC coating [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…DLC describes a broad term referring to several forms of amorphous carbon (hydrogenated [a‐C:H] and hydrogen‐free [a‐C]) and can be applied in biosensors, electronics, protective coatings for mechanical and medical components, and so on . Characteristic disadvantages of DLC (poor thermal stability and high internal stresses) can be overcome by introducing metal nanoparticles to the film . By combining the best properties of matrix and filler (in our case, DLC and Ag nanoparticles, respectively), the resulting nanocomposite films have promising applications in multidisciplinary fields of mechanics, optics and photonics, electronics, and medicine …”
Section: Introductionmentioning
confidence: 99%